Nitrogen applied in okra under non-tightness grown and residual fertilization - Cardoso,Marinice O (2012)
The aim of this study was to evaluate, in the Amazonian rainy season, the effect of nitrogen applied in okra under non-tightness grown and residual fertilization. The trial was carried out in the Embrapa Amazonia Ocidental, in Iranduba, Amazonas state, Brazil, between October/2010 and February/2011, in dystrophic Yellow Argisoil, medium texture, using pits with residual fertility. The experimental design was of randomized blocks with four repetitions (two lines with four plants, spacing of 1.5x1.0 m) and four main treatments (urea: 0.0; 20.0; 40.0 and 60.0 g plant-1 corresponding to 0.0; 60.0; 120.0 and 180.0 kg ha-1 of N, respectively, in two portions) using cv Dardo. Besides two additional treatments: chicken manure (1.0 L pit-1, with the cv Dardo) and cv Santa Cruz-47 (with urea rate of 40.0 g plant-1). Micronutrients in pits and dripping system irrigation were applied. All the studied traits had significant quadratic response with the increase of the urea rates. The highest estimated value for the plant height (39.7 cm), canopy diameter (86.2 cm), fruit number (36.0 un plant-1), fruit average mass (17.3 g), harvest number within production cycle (26.4 un cycle-1) and of the yield (4051 kg ha-1) were observed with (g plant-1 of urea): 48.3; 43.5; 38.5; 49.7; 32.7; and 40.5, respectively. Those original traits contributed reasonably poised for plant overall performance (PC1), but subordinate there was antagonism between harvest number and fruit number versus fruit average mass and canopy diameter (PC2). The chicken manure showed positive response compared to the control treatment, but didn't differ from urea rates for all these characteristics. When compared to cv Dardo, the cv Santa Cruz-47 only presented higher values to canopy diameter and number of harvests. The economical efficiency maximum dose was 40.2 g plant-1 of urea (120.6 kg ha-1 of N), with net income per hectare equal to 2.09 tons of okra fruits.